2013
DOI: 10.1007/s11769-013-0641-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crude oil contamination on soil physical and chemical properties in Momoge wetland of China

Abstract: Large oilfields are often coincidentally located in major river deltas and wetlands, and potentially damage the structure, function and ecosystem service values of wetlands during oil exploration. In the present study, the effects of crude oil contamination during oil exploration on soil physical and chemical properties were investigated in marshes of the Momoge National Nature Reserve in Jilin Province, China. The concentrations of total petroleum hydrocarbons in the marsh soil near the oil wells are signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
81
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(102 citation statements)
references
References 31 publications
18
81
1
2
Order By: Relevance
“…The soil analysis indicated a slight impact of gas oil and kerosene on the soil pH, and it had a tendency to shift toward neutral (Vonloocke et al 1975; Ahmadi et al 1996) and caused the cumulative enhancement in the soil respiration (Fallah et al 2012b;Labud et al 2007), increase in the BD (Kayode et al 2009), organic matter (Okonokhua et al 2007;Wang et al 2013), and the reduction in the soil porosity (Kayode et al 2009) and the electrical (Benka-Coker and Ekunday 1995) and saturated hydraulic conductivity; moreover, the BTC results revealed that the gas oil retention was significantly more than that of kerosene and kerosene flowed out of the soil by sharper gradient and less retardation especially in the application of higher amount of kerosene (Wang et al 2000;Wang and Shao 2009). The reason is that the reactivity of gas oil with the silty clay soil is substantially more than that of kerosene which is probably because of the structural form and its carbonic chain number, and on the other hand, it caused more intense surface absorption (Fallah et al 2012a(Fallah et al , 2013.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil analysis indicated a slight impact of gas oil and kerosene on the soil pH, and it had a tendency to shift toward neutral (Vonloocke et al 1975; Ahmadi et al 1996) and caused the cumulative enhancement in the soil respiration (Fallah et al 2012b;Labud et al 2007), increase in the BD (Kayode et al 2009), organic matter (Okonokhua et al 2007;Wang et al 2013), and the reduction in the soil porosity (Kayode et al 2009) and the electrical (Benka-Coker and Ekunday 1995) and saturated hydraulic conductivity; moreover, the BTC results revealed that the gas oil retention was significantly more than that of kerosene and kerosene flowed out of the soil by sharper gradient and less retardation especially in the application of higher amount of kerosene (Wang et al 2000;Wang and Shao 2009). The reason is that the reactivity of gas oil with the silty clay soil is substantially more than that of kerosene which is probably because of the structural form and its carbonic chain number, and on the other hand, it caused more intense surface absorption (Fallah et al 2012a(Fallah et al , 2013.…”
Section: Resultsmentioning
confidence: 99%
“…The most increase in the soil organic matter was related to one pore volume of gas oil, half pore volume of gas oil, one pore volume of kerosene, and half pore volume of kerosene, respectively, in the early time after the contamination. The results of various researches on the effects of petroleum distribution showed an increase in the organic carbon and organic matter in the petroleum-polluted soils (Okonokhua et al 2007;Wang et al 2013). …”
Section: The Effect Of Gas Oil and Kerosene On The Soil Phmentioning
confidence: 99%
“…USA (Leewis et al, 2013;Horel et al, 2014), Canada (Akbari and Ghoshal, 2014), Argentina (Rios et al, 2014), Italy (Giampaolo et al, 2014), Romania (Marinescu et al, 2014), China (Fu et al, 2014;Wang et al, 2013), Malaysia (Hamzah et al, 2014), India (Yenn et al, 2014), Iran (Khamehchiyan et al, 2007;Rad et al, 2014) and Kuwait (Al-Mailem et al, 2014). The problem is most notable in the Niger Delta region, Nigeria (Onojke and Frank, 2013), where an estimated average of 240,000 barrels of crude oil is spilled every year (Ordinioha and Brisibe, 2013) and is listed among the top ten toxic threats (Blacksmith Institute, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of high molecular weight compounds with very low solubility in water prevents natural biodegradation process from working efficiently in hydrocarbon contaminated soils (Esin and Ayten, 2011). Oil usually causes anaerobic environment in soil by smothering soil particles and blocking air diffusion in the soil pores, and these affects soil microbial communities (Wang et al, 2013). These compounds also penetrate macro-and micro-pores in soil limiting water and air transport that would be necessary for organic matter conversion.…”
mentioning
confidence: 99%
“…The daily maximum surface temperature of hydrocarboncontaminated soils is often higher than that of adjacent control sites. Heavy crude oil pollution can cause complete mortality of marsh vegetation (Wang et al, 2013).…”
mentioning
confidence: 99%